2023
DOI: 10.1039/d3ra03977c
|View full text |Cite
|
Sign up to set email alerts
|

The volatile release evaluation of nicotine from snus products under different storage conditions based on surface-enhanced Raman spectroscopy technology

Abstract: The volatile release evaluations of nicotine of snus products under different storage conditions were performed based on Fe3O4 microparticles coated with Au nanorods and Au nanoparticles (Fe3O4@AuNRsNPs) as SERS substrates combined with capillary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…For instance, Tian et al. (2023) coated Fe 3 O 4 microparticles with Au nanorods and nanoparticles for the SERS‐based detection of volatile nicotine from snus products [132] . By loading the nanocomposites into capillaries and varying storage conditions, the study found that higher temperature and humidity significantly accelerated nicotine release, evidenced by an increase in the SERS signal.…”
Section: Sers‐based Applications Of Magnetic–plasmonic Nanocompositesmentioning
confidence: 99%
“…For instance, Tian et al. (2023) coated Fe 3 O 4 microparticles with Au nanorods and nanoparticles for the SERS‐based detection of volatile nicotine from snus products [132] . By loading the nanocomposites into capillaries and varying storage conditions, the study found that higher temperature and humidity significantly accelerated nicotine release, evidenced by an increase in the SERS signal.…”
Section: Sers‐based Applications Of Magnetic–plasmonic Nanocompositesmentioning
confidence: 99%